The danger of misinformation in based on real events fiction: The Thing About Pam (or the thing about justifying the criminal) - Gastón Lorente, Lucía; Gómez-Baceiredo, Beatriz (Estudios sobre el Mensaje Periodístico, 2022)
This article compares the NBC miniseries The Thing About Pam (2022) with the podcast on which it is based in order to decide if fiction can misinform the audience through the characterization of characters that are based on real people. The miniseries is a prime example of a recent trend: the production of fictions that are based on journalistic works and that tell the story about women that have committed a crime. After accomplishing a comparative and interpretative analysis about the series' main character characterization, we conclude that the fiction reinforces the features already set out by the podcast, but somehow justify the behavior of the main character with an explanation that has nothing to do with the podcast’s findings. This justification together with the use of the same narrator in both works may misinform the audience about a real story whose trial has not been held yet.
Keywords: Fiction; based on real events; podcast; journalism; misinformation